NILAI PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK MORAL SANTRI SMA DI PONDOK PESANTREN MODERN AL-KHAIRAT SINIU KECAMATAN SINIU KABUPATEN PARIGI MOUTONG - Yasir Arafat; Nur Atika; Irfandi Irfandi; Ufiyah Ramlah (CV. ALIM'SPUBLISHING, 2024)
Islamic education has great noble values ​​and is able to determine position and function in society. The values ​​of Islamic education are the most important thing and should be implemented and maintained by followers of the Islamic religion. The values ​​of Islamic education are taught to students not to be memorized into knowledge, but to be internalized and practiced in everyday life. This research aims to find out more broadly and in depth the Internalization of Islamic Religious Values ​​in Shaping the Character of Santri, with the following coverage: (1) The process of internalizing Islamic religious values ​​in forming the character of santri (2) The method of internalizing Islamic religious values ​​in forming character of santri (3) The impact of internalization of Islamic religious values ​​in shaping the character of santri.The research was carried out at the Al-Khairat Siniu Modern Islamic Boarding School using a qualitative approach with a case study type. Data collection was carried out using interviews. Data analysis techniques include data reduction, data presentation, and drawing conclusions. To check the validity of the data, researchers used triangulation techniques. Meanwhile, the informants in this research were Ustadzah and Santriwati.The results of the research show that Islamic religious values ​​at the Al-Khairat Siniu Islamic Boarding School, including aqidah values, shari'ah values ​​and moral values, have become a value that is internalized in the daily life of students at the Islamic boarding school. This needs to be done with istiqomah in implementing it, because the internalization of Islamic religious values ​​is not something instant but is something that requires a process, so this of course requires a process, so this of course requires certain efforts made by the council of kyai or ustadz as well as the santri council in achieving successful internalization of Islamic religious values ​​in order to shape the character of the students.